Bahasa Gaul Remaja Milenial di Twitter: Tren, Makna, dan Tantangan bagi Bahasa Indonesia - Simorangkir, Nomi Agustina; Saragih, Elza L. L; Aritonang, Cynthia; Marbun, Oktavia Dewita (Journal of Social Movements, 2025)
The phenomenon of slang use among millennial teenagers on Twitter is interesting to study because it affects communication patterns and sensitivity to good and correct Indonesian language. This study aims to describe the form, meaning, and impact of slang use on millennial teenagers on social media. The research was conducted using descriptive qualitative approach through content analysis method. Data were collected using listening, note-taking, and screen capture techniques on tweets containing popular slang words, abbreviations, or acronyms. The results showed that teenagers use acronyms such as otw, baper, and bucin as a symbol of familiarity and group identity. However, the excessive use of slang has an impact on the decline in the ability to compose formal sentences according to Indonesian language rules. This finding indicates the need for language coaching for teenagers to be able to place slang appropriately without reducing formal literacy skills. The implication of this research is expected to be an input for parents, educators, and the government in formulating strategies for developing Indonesian language in the digital era.